PERINATAL WELLBEING IN AN ABORIGINAL CONTEXT: UNDERSTANDING THE HEALTH BELIEFS AND CULTURAL PERCEPTIONS OF GRANDMOTHERS FROM THE SIX NATIONS RESERVE IN SOUTHERN ONTARIO - KANDASAMY, SUJANE (My University, 2015)
Background: Aboriginal peoples face disproportionate health inequalities in comparison to non-Aboriginal Canadians, especially in regards to cardiovascular disease risk factors. Evidence illustrates that the propensity to develop these chronic diseases happens during the perinatal period. Related to this are maternal health behaviours—which are influenced by grandmothers’ advice. Very few studies have explored Aboriginal grandmothers’ beliefs around perinatal health or how they translate into maternal health behaviours. Objectives: The objectives of this thesis were to: 1) Qualitatively explore the beliefs and cultural perceptions around prenatal and postnatal health behaviours from the accounts of Grandmothers from the Six Nations reserve; 2) Incorporate the emergent themes to develop a theoretical framework; 3) Design and apply culturally-respectful avenues for knowledge translation. Methods: Qualitative, semi-structured individual interviews and focus groups were conducted with grandmothers from the Six Nations reserve. Sampling of participants used non-probabilistic methods. Recruitment was achieved through the leadership of community members and continued until saturation. All interviews were audio-recorded, transcribed verbatim, and underwent thematic analysis. A Six Nations community member was involved with the coding process and additional interviews were conducted to ensure member-checking. Results: Six Nations grandmothers identified three primary perinatal beliefs: 1) Pregnancy is a natural phase of the life course that is not an illness nor a “comfort zone”; 2) Pregnancy is a sacred period where balance is key; 3) Optimal perinatal health is achieved through immunity, security, comfort, social development, and parental responsibility. This knowledge is shared via storytelling and observational teaching. In addition, the grandmothers identified local community responsibilities required to uphold optimal health. Consultation with the community resulted in an integrated knowledge translation component (short film) for key stakeholders. Conclusion: Building resilience and strength through culturally-generated interventions will guide the future of community-based programs and policies that aim to reduce cardiometabolic risk factors in this Aboriginal community.
Keywords: Perinatal health; Aboriginal Health; Qualitative Research; Constructivist Grounded Theory; Grandmothers' advice